2012
DOI: 10.1111/acps.12057
|View full text |Cite
|
Sign up to set email alerts
|

Atypical depression and alcohol misuse are related to the cardiovascular risk in the general population

Abstract: To conclude results emphasize the need to subtype depression and to pay particular attention to the atypical subtype. Comorbid alcohol misuse may further increase the cardiovascular risk. Efforts to diminish smoking in subjects with mental disorders could be crucial measures to reduce their high incidence of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 55 publications
3
54
1
3
Order By: Relevance
“…The same results were found for lifetime, current, and past depression. In a Swiss cross-sectional study, atypical depression was associated with increased prevalence of overweight (Glaus et al, 2013). Also, Levitan et al (2012), using data from the National Epidemiologic Survey on Alcohol and Related Conditions, demonstrated that subjects with atypical depression had markedly elevated obesity rates compared to population controls and other depressed subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The same results were found for lifetime, current, and past depression. In a Swiss cross-sectional study, atypical depression was associated with increased prevalence of overweight (Glaus et al, 2013). Also, Levitan et al (2012), using data from the National Epidemiologic Survey on Alcohol and Related Conditions, demonstrated that subjects with atypical depression had markedly elevated obesity rates compared to population controls and other depressed subjects.…”
Section: Discussionmentioning
confidence: 97%
“…A positive association between depression, especially atypical one, and obesity has been demonstrated in both longitudinal Lasserre et al, 2014) and cross-sectional studies Glaus et al, 2013;Chou and Yu, 2013). A reciprocal link between depression and obesity was suggested: obesity was found to increase the risk of clinically diagnosed depression, and depression was found to be predictive of developing obesity.…”
Section: Introductionmentioning
confidence: 92%
“…Aside from the anti-platelet aggregation activity of aspirin and the lipid-lowering function of statins, these medications have been postulated to have anti-inflammatory properties (Antithrombotic Trialists et al, 2009;Antonopoulos et al, 2012). Depression has been found to be associated with an increased cardiovascular risk (Baune et al, 2012;Glaus et al, 2013;Penninx et al, 2013) and low-grade chronic inflammation is a possible mechanism that could underlie this association (Baune et al, 2012). Hence, it has been suggested that the regular use of aspirin or statins could be protective against depression (Berk et al, 2013;Stafford and Berk, 2011;While and Keen, 2012;Parsaik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation as part of the innate immune response has been postulated to be one mechanism (Baune et al, 2012;Dinan, 2009;Vogelzangs et al, 2013) underlying the welldocumented associations of mental disorders with cardiovascular risk factors (CVRFs) (Glaus et al, 2013;Van Reedt Dortland et al, 2013) and cardiovascular diseases (CVD) (Baune et al, 2012). Proinflammatory cytokines such as interleukin (IL)-1b, IL-6 or tumor necrosis factor (TNF)-a (Dowlati et al, 2010;Mota et al, 2013) induce the production of acute-phase proteins including the Creactive protein (CRP) (Maes et al, 1997), which is a common marker of underlying low-grade inflammation (Ford and Erlinger, 2004).…”
Section: Introductionmentioning
confidence: 99%